Cost-effectiveness of adding Endocuff® to standard colonoscopies for interval colorectal cancer screening - Yu TM; Tradonsky A; Tang J; Arnold RJG (Dove Medical Press, 2019)
Tiffany M Yu,1 Alison Tradonsky,1 Jun Tang,1 Renée JG Arnold1,21Department of Life Sciences, Navigant Consulting, Inc, San Francisco, CA, USA; 2Department of Environmental Medicine and Public Health, Icahn School of Medicine at Mount Sinai, New York, NY, USABackground and aims: Higher screening colonoscopy adenoma detection rates (ADRs) correlate with reduced risk of interval colorectal cancer (CRC). The Endocuff® device has been shown to improve ADRs compared to standard colonoscopy (SC). This cost-effectiveness analysis compared interval CRC screening using Endocuff®-assisted colonoscopy (EC) vs SC.Methods: A decision-analytic Markov model followed patients through screening, CRC diagnosis, progression, remission, and death. ADRs, CRC progression, and utilities were from literature. CRC incidence, stage distribution, and mortality were from the Surveillance, Epidemiology, and End Results (SEER) and SEER-Medicare linked databases. Screening and annual patient costs were from public databases and literature. Endocuff® device average sales price was applied. Lifetime device and medical costs were evaluated separately for device purchaser, health plan, and accountable care organization (ACO) perspectives.Results: Consistent use of EC instead of SC was expected to reduce lifetime risks of interval CRC and related death by 0.98% and 0.19%, respectively, preventing one case per 102 patients and one death per 526 patients. Survival and quality-of-life (QoL) improved by 0.025 life-years and 0.011 quality-adjusted life-years (QALYs) per patient on average. EC instead of SC led to incremental cost-effectiveness ratios to the device purchaser of $4,421 per life-year gained and $9,843 per QALY gained, and $199 or $87 average cost-savings per patient to the health plan or ACO, respectively.Conclusion: Endocuff® for screening colonoscopies was expected to reduce interval CRC incidence and death, improve QoL, and be cost-effective to the device purchaser and cost-saving to a health plan or ACO.Keywords: adenomatous polyps, colorectal neoplasm, colonic polyps, adenocarcinoma, interval cancer